Endoscopic treatment of biliary fistulas: results of 20 patients - Fatih HİLMİOĞLU and Bülent YILDIRIM and Melih KARINCAOĞLU and Murat ALADAĞ and Bülent KANTARÇEKEN and İbrahim DOĞAN (Turkish Journal of Gastroenterology, 2019)
-